The Effect of Environmental Social Governance Disclosure and Capital Structure on Company Value in Mining Sector Companies Listed on the Indonesian Stock Exchange - Zen, Sri Daryanti; Luthan, Elvira; Hujnir, Putri Arinda (Dinasti International Journal of Economics, Finance & Accounting, 2025)
This study aims to evaluate the effect of “Environmental, Social, and Governance (ESG) disclosure and capital structure on firm value”. The research object includes companies listed on the IDX during the period 2020 to 2023. The approach used is quantitative with a causal research design, and sample collection is done through purposive sampling method, resulting in 80 companies as research objects. The information used in this analysis comes from the Indonesia Stock Exchange website (www.idx.ac.id). The data analysis process was carried out using SPSS version 29 software, which includes “descriptive statistical analysis, classical assumption testing, and multiple linear regression analysis” to test the relationship between variables. The findings reveal that ESG disclosure, assessed through the ESG index, does not significantly impact firm value. In contrast, the capital structure, represented by the Debt to Equity Ratio (DER), has a significant and positive impact on firm value.